Factors Affecting Prognosis and Survival in Extremity Osteosarcoma - Dharanikota, Anvesh (Indian J Surg Oncol, 2021)
BACKGROUND: Osteosarcoma is a malignant bone tumor affecting mainly children and young adults and commonly involves extremities. The aim of this study was to assess the patient-related, tumor-related, and treatment-related factors affecting the overall survival in patients with non-metastatic extremity osteosarcoma. METHODOLOGY: A retrospective, single institutional study of 100 patients with non-metastatic extremity osteosarcoma was done between 2014 and 2019. Age, sex, histologic type, tumor site, use of preoperative chemotherapy and its duration, response to chemotherapy, type of surgery, presence of local recurrence, occurrence of lung metastasis, and survival data were recorded. Survival analysis was done using Kaplan-Meier method. p < 0.05 by log-rank test was considered statistically significant. Statistical data were analyzed using SPSS v.25(IBM). RESULTS: The median age of presentation was 18 years with male sex preponderance. The most common site of presentation was distal femur, and commonest histological variant was osteoblastic osteosarcoma. Incidence of local recurrence was 9%, and lung metastasis was identified in 12% on follow-up. The 5-year overall survival (OS) was 65.5%, and 5-year local recurrence-free survival was 57.6%. The 5-year OS in neoadjuvant chemotherapy group was 80% compared to 39.5% in upfront surgery group (p = 0.015). The 5-year OS in patients with tumor necrosis > 90% and < 90% was 93.2% and 71.2%, respectively (p = 0.038). The 5-year OS in patients without lung metastasis was 76%, whereas none who developed lung metastasis has survived 5 years (p < 0.001). CONCLUSION: The use of neoadjuvant chemotherapy, good response to chemotherapy, and the absence of lung metastasis on follow-up can independently predict better overall survival.